2020
DOI: 10.3390/catal10040461
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Effects of Cobalt Oxides on Ni/Co-Embedded Al2O3 for Hydrogen-Rich Syngas Production by Steam Reforming of Propane

Abstract: The synergetic effects of Co oxides on the Ni/CoAl (NCA) catalysts were observed at an optimal molar ratio of Al/Co = 2 (NCA(2)) due to the partial formations of thermally stable spinel CoAl2O4 phases for the steam reforming of propane (SRP). The optimal content of the spinel CoAl2O4 phases on the NCA(2) was responsible for the formation of the relatively active oxophilic metallic Co nanoparticles with a smaller amount of less active NiAl2O4 on the surfaces by preserving the relative amount of metallic Co of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
3
0
0
Order By: Relevance
“…A higher distribution of active metal leads to a stronger interaction and hence shifts the reduction peak to a higher reduction temperature region. 35 Another reason for the peak broadness is due to the collective formation of metal-aluminate species under higher calcination temperature, 31,36 and the results are concurrent with the XRD results. The hydrogen consumption is shown in Table 2.…”
Section: Resultssupporting
confidence: 66%
“…A higher distribution of active metal leads to a stronger interaction and hence shifts the reduction peak to a higher reduction temperature region. 35 Another reason for the peak broadness is due to the collective formation of metal-aluminate species under higher calcination temperature, 31,36 and the results are concurrent with the XRD results. The hydrogen consumption is shown in Table 2.…”
Section: Resultssupporting
confidence: 66%
“…Based on other studies, the reduction of alumina supported nickel-based catalysts to metallic nickel occurs at temperatures < 600 °C [21,22]. Supporting this, our results demonstrated that the which may form as a result of the interaction of the metals with the alumina support [23,24]. CO 2 -TPD analysis was carried out to identify the number of basic sites present on the oxidized catalysts (Fig.…”
Section: Catalyst Characterizationsupporting
confidence: 78%
“…The average diameters of the metal oxide particles are 3.5, 7.5, 13.7, 15.1 and 17.5 nm for Fe/NOMC, Fe2Co/NOMC, FeCo/NOMC, Fe0.5Co/NOMC, and Co/NOMC, respectively. Therefore, the incorporation of cobalt dramatically increases the particle size of the metal oxide, as discovered previously [39,40] S7. The elemental compositions were quantified and are listed in Table 1.…”
Section: Resultssupporting
confidence: 55%